Future change in ocean productivity: Is the Arctic the new Atlantic?1. Issue 12 (12th December 2015) - Yool, A.; Popova, E. E.; Coward, A. C.
Abstract: One of the most characteristic features in ocean productivity is the North Atlantic spring bloom. Responding to seasonal increases in irradiance and stratification, surface phytopopulations rise significantly, a pattern that visibly tracks poleward into summer. While blooms also occur in the Arctic Ocean, they are constrained by the sea‐ice and strong vertical stratification that characterize this region. However, Arctic sea‐ice is currently declining, and forecasts suggest this may lead to completely ice‐free summers by the mid‐21st century. Such change may open the Arctic up to Atlantic‐style spring blooms, and do so at the same time as Atlantic productivity is threatened by climate change‐driven ocean stratification. Here we use low and high‐resolution instances of a coupled ocean‐biogeochemistry model, NEMO‐MEDUSA, to investigate productivity. Drivers of present‐day patterns are identified, and changes in these across a climate change scenario (IPCC RCP 8.5) are analyzed. We find a globally significant decline in North Atlantic productivity (> −20%) by 2100, and a correspondingly significant rise in the Arctic (> +50%). However, rather than the future Arctic coming to resemble the current Atlantic, both regions are instead transitioning to a common, low nutrient regime. The North Pacific provides a counterexample where nutrients remain high and productivity increases with elevated temperature. These responses to climate change in the Atlantic and Arctic are common between model resolutions, suggesting an independence from resolution for key impacts. However, some responses, such as those in the North Pacific, differ between the simulations, suggesting the reverse and supporting the drive to more fine‐scale resolutions. Key Points: Across 21st century, N. Atlantic productivity significantly declines while increasing in the Arctic Despite disparate climate change responses, regions share underlying convergence in nutrient status Results broadly consistent between different model resolutions though they differ in subbasin detail